Photosynthesis regulation by sucrose metabolism under water deficit and source-sink alterations in sugarcane - Lobo, Ana Karla Moreira (2016)
LOBO, A. K. M. Photosynthesis regulation by sucrose metabolism under water deficit and source-sink alterations in sugarcane. 2016. 118 f. Tese (Doutorado em Bioquímica)-Universidade Federal do Ceará, Fortaleza, 2016.